The Moderating Effects of Board Independence and the Separation of Chairman–Chief Executive Officer Duality Roles on a Firm’s Value: Evidence from the Thai Listed Firms - Wonlop Writthym Buachoom; Yot Amornkitvikai (Global Business Review, 2022)
Since the 1997 financial crisis, good corporate governance is one of the most contentious problems for Thai listed companies’ long-term viability. Unlike earlier research in Thailand, this article uses a three-level hierarchical regression model to examine the moderating effects of board independence and the separation of chairman–chief executive officer (CEO) duality roles on the firm’s value of the Thai listed firms between 2010 and 2019. This study confirms a negative relationship between family ownership and a firm’s value in Thailand. Nevertheless, it reveals that the association between family ownership and firm’s value becomes positive if the Thai listed firms have a high proportion of independent directors. Further evidence confirms that the separation of chairman–CEO duality roles can increase a firm’s value, but it cannot solely enhance the value in those firms with high family ownership. Finally, this study discusses empirically-based practical implications and recommendations.
Keywords: Corporate Finance and Governance; Family Business Performance and Succession; Working Capital and Financial Performance